The brazilian family in a cultural view - Maria Grasiela Teixeira Barroso; Maria de Fátima Cardoso Marques; Nara Sibério Pinho Silveira; Patrícia Neyva da Costa Pinheiro (Rev Rene)
The present study makes an approach on family and its structure, seeking the retaking of concepts in a cultural view. Starting from the researched concepts we can find some reflections on the history of the Brazilian family, culture, doubts and perspectives around its rights. It was investigated about family conceptions, family culture, Brazilian family, and cultural permanences. Besides the investigative search in the libraries, was used the INTERNET and official documents. Several authors make comments about the public politics when they refer that the family still needs to be seen in a more privileged and central position in the guidelines and in the programs of the Brazilian social public politics. They also comment that the fight for the survival imposes member’s submition to any work type, being the culture decisive in the way a family constitutes itself. The family is understood as a social institution, an all articulated whole relacional, constituted by the social, active man, permeated by the social structure, of classes. Thus, this study supports the understanding that the family, in different forms, reflects an society ordering, which needs to be firm in a base of solid sustentation. And to understand the family, one should not break it into fragments, as well as the economy or the political system that are unique, the family needs to be worked and seen in its totality.